Thermo-physical properties of rubber seed useful in the design of storage structure - Fadeyibi, Adeshina; Osunde, Z D (International Journal of Agricultural and Biological Engineering, 2012)
A. Fadeyibi*, Z. D. Osunde(Department of Agricultural and Bioresources Engineering, Federal University of Technology, Minna, Nigeria)Abstract: This study was carried out to determine the thermo-physical properties of rubber seed in the moisture range of 9.1% to 14.8% (w.b.). The length, width, thickness, measured surface area, bulk density and true density increased with increasing moisture content with high coefficients of determination. Their optimum values at 14.8% moisture content were 17.00 mm, 11.94 mm, 8.26 mm, 285.20 mm2, 295.00 kg/m3 and 470.67 kg/m3, respectively. The angle of repose increased as moisture content increased with low coefficient of determination and has optimum value of 28.81